(untitled) (Swiss Medical Weekly, 2017)
AIM Postpartum haemorrhage (PPH) is one of the leading causes of maternal morbidity and mortality. Studies have reported an increase in incidence of postpartum haemorrhage in recent years. Our goal was to investigate changes in the incidence of postpartum haemorrhage (PPH) and its risk factors in Switzerland from 1993 to 2014. METHODS This population-based retrospective cohort study used data from the national Swiss Hospital in-patient database for obstetric and gynaecological hospital admissions – “Arbeitsgemeinschaft Schweizer Frauenkliniken” (ASF Statistik). All patients with deliveries between January 1993 and December 2014 were included. We used the database codes to identify patients with PPH, maternal factors, pregnancy-related and delivery-related factors. Significant changes in temporal trends were determined using Mantel-Haenszel test for trend. Multivariable logistic regression analyses were conducted to assess PPH and risk factors. RESULTS Births complicated by PPH in Switzerland increased from 2.5% in 1993 to 4.5% in 2014 (p <0.001), paralleled by an increase in uterine atony. Failure to progress during the second stage of labour (odds ratio [OR] 1.5, 95% confidence interval [CI] 1.5–1.6), oxytocin augmentation (OR 1.2, 95% CI 1.2–1.3), vacuum extraction (OR 1.1, 95% CI 1.1–1.2), and especially abnormally invasive placenta (OR 10.4, 95% CI 9.5–11.5) and placenta praevia (OR 4.9, 95% CI 432–5.6) were factors with the highest risk for postpartum haemorrhage. CONCLUSIONS Postpartum haemorrhage is a relatively common and potentially dangerous obstetric complication with increasing incidence over the last two decades in Switzerland. Its increase over time has been paralleled by an increase in uterine atony.